Hindu Spiritual Tourism Branding: The AKIELS Analysis of the Self-Healing Program through the Melukat Ritual at Tirta Empul Temple, Bali - Sarah Khaerunnisha Fathiarani; Eli Jamilah Mihardja (Jobmark: Journal of Branding and Marketing Communication, 2024)
The presence of spiritual tourism in the form of a hugging process, known as a self-cleansing ritual for Hindus, has now become much sought after by local and foreign tourists. The Melukat ritual, a sacred Hindu practice, involves a series of cleansing and purifying activities in a holy water spring, believed to provide spiritual and physical healing. This process provides benefits, namely self-healing from stress, trauma, depression, and so on, just by going through several believed stages. Tirta Empul Temple is the most popular Melukat location for tourists in Bali. The queue for those who want to carry out the Melukat process is always long and snakes every day, not only during the holiday season or holidays. This study focuses on observing tourist self-healing program activities through the Melukat ritual using the AKIELS Model analysis knife. The findings show that Tirta Empul Temple, in the minds of tourists, is attached to the Melukat ritual, which is believed to be self-healing for tourists because it provides calming benefits from stress, trauma, and depression. Tirta Empul Temple has become embedded in the minds of tourists, and it can be represented by the many visitors who come to do the ritual Melukat almost every day. This study produces an in-depth understanding of Hindu spiritual tourism branding by dissecting the aspects of brand awareness, knowledge, image, experience, loyalty, and spirituality in the tourist self-healing program through the Melukat ritual in Bali.